2018
DOI: 10.1002/pssb.201800143
|View full text |Cite
|
Sign up to set email alerts
|

White Neutron Holography in Pulsed Neutron Facilities

Abstract: Slight changes in atomic structures by doping foreign elements in materials play an important role in functionality. This article presents a review of the newly developed technique, white neutron holography, which is an effective probe for investigations of effects of doping on atomic structures, particularly for light elements. The principle and advantages of white neutron holography are explained. Observations of local structures around the dopant in B‐doped Si, Eu‐doped CaF2 and other materials have already… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
(58 reference statements)
0
2
0
Order By: Relevance
“…Atomic images of the local atomic structures around the B atom were reconstructed using 66 holograms with different wavelengths in the range of 0.63–3.95 Å (corresponding to the energy range of 5.23–206.0 meV). The details and principles of the white neutron holography are also reported in refs , . To characterize the crystal structure of the B-doped Mg 2 Sn SCs, SC-XRD with Mo Kα radiation (D8 QUEST, Bruker AXS) was performed using a small SC piece (typically, 30 × 60 × 70 μm 3 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic images of the local atomic structures around the B atom were reconstructed using 66 holograms with different wavelengths in the range of 0.63–3.95 Å (corresponding to the energy range of 5.23–206.0 meV). The details and principles of the white neutron holography are also reported in refs , . To characterize the crystal structure of the B-doped Mg 2 Sn SCs, SC-XRD with Mo Kα radiation (D8 QUEST, Bruker AXS) was performed using a small SC piece (typically, 30 × 60 × 70 μm 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, in this study, we investigate the effect of B-doping on the crystal structure and TE properties of Mg 2 Sn SCs, to determine whether the B dopant can be utilized for future enhancement of the zT of Sb-doped Mg 2 Sn SC. For the crystal structure analysis, we use white neutron holography, a kind of atomic resolution holography that can directly reveal a three-dimensional local structure around a dopant without any structure model. The white neutron holography exhibits higher sensitivity to light elements, such as hydrogen, B, and oxygen, compared with X-ray fluorescence holography and photoelectron holography. Thanks to the white neutron holography, we successfully revealed that the B-doping site in the Mg 2 Si SCs is the Mg site .…”
Section: Introductionmentioning
confidence: 99%